Kepuasan Warga Terhadap Perkhidmatan Kerajaan Tempatan Padangpanjang - Lanin, Dasman (2010)
The objectives of this study are to identify the system of organizational management of local governmental service in Padangpanjang, West Sumatra, particularly the system implemented after the reform era in Indonesia; to identify the aspects of citizen/customer satisfaction toward services addressed by local governmental organization in Padang panjang. These include the concepts of citizen/customer satisfaction, determinant factors of the citizen/customer satisfaction, and the role of managers in the organization. This study also aimed at describing and analyzing the organization of some Dinas (the Agencies of Local Government in Indonesia) in addressing services toward customers, like Education Agency, Health Agency, and Social Agency. This is an expost-facto study. Quantitative approach was used in this study and supported by qualitative approach in interpreting the dependent variable, that is citizen/customer satisfaction. There are six independent variables, that is delivery, timeliness, information, professionalism, staff attitude, and orgaiizational politic. Besides, there is a moderator variable that is the role of manager of local government. Data of this study were collected through questionnaires spread to 1086 respondents. The respondents were determined through stratifed proportional random sampling. Then, the data were analyzed with multi regression and partial through SPSS program. The finding of this study indicated that all independent variables were significantly correlated to dependent variables that is citizen/customer satisfaction with the local government public service, either individually or simultaneously. So was the moderator variable. However, the dependent variable of organizational politic, as a new independent variable in this model, was negatively correlated to the dependent variable. Therefore, all of alternative hypothesis in this study could be accepted. It means that all independent and dependent variables of this study could be useful for developing the science of public service management, especially in developing the determinant factors of citizen/customer satisfaction with local government services, and the finding of this study could be more practically adopted in addressing an accountable public service, that is outcome oriented public service, of local government.